2018
DOI: 10.1680/jmacr.17.00436
|View full text |Cite
|
Sign up to set email alerts
|

Alkali activation of a high MgO GGBS – fresh and hardened properties

Abstract: In this study, concretes and pastes were produced from a high MgO ground granulated blast furnace slag (MgO content 16.1 wt.%) by alkali activation with various amounts and combinations of sodium carbonate and sodium silicate. Sodium carbonate activators tended to reduce slump compared to sodium silicate at the same dose, and, in contrast to the literature for many blast furnace slags with more moderate MgO, to shorten the initial and final setting times in comparison with concretes activated by sodium silicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
4
18
0
1
Order By: Relevance
“…Both effects were observed also by others and were related to a higher pH values which accelerated dissolution of the slag [24,27,[35][36][37]. Higher alkali modulus of the used SS activator decreased the compressive strength values in both slags (Figure 9).…”
Section: K B Hmsupporting
confidence: 69%
“…Both effects were observed also by others and were related to a higher pH values which accelerated dissolution of the slag [24,27,[35][36][37]. Higher alkali modulus of the used SS activator decreased the compressive strength values in both slags (Figure 9).…”
Section: K B Hmsupporting
confidence: 69%
“…The high MgO content of the slag tends to affect the early-age properties of the binder matrix. Earlier studies, also performed by the authors, indicated formation of hydrotalcite-like Mg-Al layered double hydroxides (Bernal et al, 2016;Humad et al, 2018;Abdollahnejad et al, 2019). The consumption of Al may also contribute to the strength development.…”
Section: Resultsmentioning
confidence: 63%
“…Although, not verified experimentally, it is very likely that the dissolution rate of GBFS was higher in the heat-cured samples thus leading to a more intensive formation of calcite and gaylussite. The formation of gaylussite was shown earlier to be predominant at an early age, in high-MgO AAS binders (Humad et al, 2018). The high sodium carbonate content in the mix SC10 provided an excess of Na ions, which supported the formation of gaylussite Na 2 Ca(CO 3 ) 2 •5H 2 O (Allahverdi et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations